How Trees Grow in the Urban Environment - Mary L. Duryea; Marlene M. Malavasi (EDIS)
This document, Circular 1093, from the School of Forest Resources and Conservation at the University of Florida, explores how trees grow in urban environments. It covers the physiological processes of tree growth, including the roles of meristems, and the impact of environmental factors such as water, light, and soil compaction. The document also distinguishes between the growth patterns of gymnosperms, angiosperms, and palms, and discusses the challenges urban trees face, such as limited rooting space and environmental stress. Practical advice for promoting tree health and longevity in urban settings is provided. First published May 1993.